Canine Rabies in the Brazil-Bolivia Border Region from 2006 to 2014 - Juliana Arena Galhardo; Carla Silva de Azevedo; Bárbara Ribeiro Remonti; Vitória Machado Neres Gonçalves; Natalia Trindade Azevedo Marques; Lilian Oliveira Borges; Danielle Ahad das Neves (Ubiquity Press, 2019)
Background: After 2006 the cross-border region between the state of Mato Grosso do Sul (Brazil) and the Germán Busch Province (Bolivia) became risk areas for canine rabies antigenic variant 1, previously unknown in the Brazilian territory. Objectives: To perform a descriptive analysis of canine rabies from 2006 to 2014, analyzing the database of the official rabies diagnostic laboratory of the State Agency of Animal and Plant Health Protection of Mato Grosso do Sul. Methods: A descriptive analysis of canine rabies from 2006 to 2014 was performed using the database of the official rabies diagnostic laboratory of the State Agency of Animal and Plant Health Protection of Mato Grosso do Sul. Location, time and residence status of the animals were analyzed. Monthly frequencies were calculated as the ratio of the number of positive samples to the total of sent samples and were then statistically compared. Findings: In the period, 539 samples of nervous system from dogs and cats were sent for rabies diagnosis, of which 37 (6.9%; CI95% 5.0-9.3) canine and no positive feline samples were found positive. Twenty-four (64.9%, CI95% 48.8-78.2) positive samples were from Bolivia and 13 (31.1%, CI95% 21.8-51.2) from Brazil. Most positive animals were owned. The years 2008 and 2009 showed the highest occurrence of canine rabies, with 18 cases recorded in 2008 and 6 in 2009 (17 in Bolivia and 7 in Brazil). Annual samples sent in Brazil presented a decreasing trend (R2 = 0.53) and, over the months, a higher concentration of samples was observed between May and August (R2 = 0.69). No annual or monthly trends were observed for Bolivian samples (R2 < 0.003). Conclusions: AgV1 canine rabies due to antigenic variant 1 is still considered an endemic disease in the Brazil-Bolivia border region, requiring an international One Health Approach to mitigate canine rabies in Latin America.